Tryptase values in anaphylaxis and insect allergy. Issue 5 (October 2019) - Bonadonna, Patrizia; Scaffidi, Luigi; Boni, Elisa
Abstract : Purpose of review: To recognize the relevance of serum tryptase measurement as a useful tool for the diagnosis of allergic diseases and mast cell disorders. Recent findings: Recent data on the role of mast cells and tryptase in allergic and other diseases provide new understanding into the mechanisms and causes of anaphylaxis. Summary: Measurement of transiently elevated tryptase levels shortly after a severe reaction can help elucidate mechanism behind the reaction in identifying mast cell activation. Hymenoptera venom allergy represents an important cause of morbidity and mortality worldwide. Venom allergy is a typical IgE-mediated reaction because of sensitization to one or more allergens of the venom, and accounts for 1.5–34% of all cases of anaphylaxis. There is a preferential association between insect venom allergy and mastocytosis. The diagnosis of a clonal mast cell disease leads to therapeutic consequences concerning the treatment of venom allergy. In conclusion, baseline tryptase levels support the clinical diagnosis of anaphylaxis and mast cell disorders, determine venom immunotherapy treatment and are relevant in deciding on lifelong treatment.